5
$\begingroup$

Given the value of sinh(x)

for example sinh(x) = 3/2

How can I calculate the value of cosh(x) ?

$\endgroup$
  • 11
    $\begingroup$ Use identity: $\cosh^2(x)-\sinh^2(x)=1$ $\endgroup$ – alans Jul 11 '14 at 18:47
  • 5
    $\begingroup$ @alans When you hover your mouse over "add comment" you will see the following: Use comments to ask for more information or to suggest improvements. Avoid answering questions in comments. $\endgroup$ – Fly by Night Jul 11 '14 at 19:26
13
$\begingroup$

Use the identity $\cosh^2x-\sinh^2x \equiv 1$. If $\sinh x = \frac{3}{2}$ then $$\cosh^2x - \left(\frac{3}{2}\right)^{\! 2} = 1$$ $$\cosh^2x - \frac{9}{4} = 1$$ $$\cosh^2x = \frac{13}{4}$$ It follows that $\cosh x = \pm\frac{1}{2}\sqrt{13}$. Since $\cosh x \ge 1$ for all $x \in \mathbb{R}$ we have $\cosh x = \frac{1}{2}\sqrt{13}$.

$\endgroup$
  • $\begingroup$ Please explain the downvote. $\endgroup$ – Fly by Night Jul 11 '14 at 18:51
  • $\begingroup$ You made a sign error. $\sinh$ maps $\mathbb{R}$ onto itself. $\endgroup$ – Ian Jul 11 '14 at 18:51
  • $\begingroup$ I think you want $\sinh x = \frac{3}{2}$ in your premise, not $\sinh^2$. (I tried to edit but it wasn't substantial enough since it was only two characters.) $\endgroup$ – Ismail Badawi Jul 11 '14 at 20:11
  • $\begingroup$ @IsmailBadawi You should not edit other people's posts. $\endgroup$ – Fly by Night Jul 11 '14 at 20:52
  • 8
    $\begingroup$ @FlybyNight Stack Exchange disagrees with you: meta.stackexchange.com/questions/120576/… $\endgroup$ – Ismail Badawi Jul 11 '14 at 21:15
9
$\begingroup$

The trick is....

$$\cosh^2x-\sinh^2x=1$$

$\endgroup$
1
$\begingroup$

Most books I have seen use this way to solve this problem using the same identity mentioned in the accepted answer: $$\sqrt{1+\sinh^2x}=\cosh x$$

$\therefore \sqrt{1+(\frac{3}{2})^2}=\cosh x$

$ \frac{\sqrt{13}}{2}=\cosh x$

$\endgroup$
0
$\begingroup$

Using $\cosh^2x-\sinh^2x=1$ you can evaluate it.

But unlike circular trig functions, there is only a single value for

$ \cosh( \sinh^{-1}(x)) $

$\endgroup$
-2
$\begingroup$

Do you want to say that $cosh^2x-sinh^2x=1$? Yes that is correct because of this: $1/4[e^{2x}+2+e^{-2x}-e^{2x}+2-e^{-2x}]= 1/4 \times 4=1$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.